The role of newspapers in the formation of gendered national identity: Polish coverage of women's and men's basketball championships. (May 2019) - Jakubowska, Honorata; Ličen, Simon
This study examines how newspapers in post-communist Poland nurture a gendered national identity through their disparate coverage of men's and women's European basketball championships. Agenda-setting, framing and social identity theories were used to analyse 502 articles published between 2009–2013. Results show that men's tournaments received 3.5 times more coverage than women's events; the gap further widened when Poland hosted the championships. Articles about men's championships were also longer (314 words on average versus 161). The discourse surrounding women's competitions was factual whereas the men's national team's performances were framed as challenges, matters of national pride, and involved combat and military terminology. Peculiarly, the most frequently mentioned member of the women's team was its male coach. Findings indicate a significant departure from the communist-era promotion of gender equality and women's empowerment as a source of pride. National identity is nurtured through newspaper coverage of the men's national team (when team colours and the first person plural are mentioned) but not of the women's national team.